PENGARUH PEMBERIAN GIBERELLIN TERHADAP PERTUMBUHAN BIBIT AREN (Arenga pinnata Merr) - Prima Irawan; Lollie A. P. Putri Agustina P Putri; Yusuf Husni (Jurnal Agroekoteknologi, 2013)
The effect of giberellin on growt of sugar palm in nursery (Arenga pinnata Merr). Application of giberellin were done to know effect on the growth of sugar palm seed. The research  used randomized block design with 5 levels of  0 ppm, 50 ppm, 100 ppm, 150 ppm, and 200 ppm. The parameters observed were seed height, leaf sum, leaf chlorophyl, steam diametre, wide leaf, fresh weight of crown, fresh weight of root, dry weight of crown and dry weight of root. The result of research showed that effect of giberellin  significantly on  seed height 10, 12, 14 weeks after planting and the optimum concentrate was on 200 ppm and not significantly number of leaf, chlorofil content, steam diametre, wide leaf, fresh weight of shoot, fresh weight of root, dry weight of shoot and dry weight of root.   Keywords : sugar palm, giberellin, growth.